2022
DOI: 10.1136/bmjopen-2021-057530
|View full text |Cite
|
Sign up to set email alerts
|

Participatory mental health interventions in low-income and middle-income countries: a realist review protocol

Abstract: IntroductionThe launch of the Movement for Global Mental Health brought long-standing calls for improved mental health interventions in low-and middle-income countries (LMICs) to centre stage. Within the movement, the participation of communities and people with lived experience of mental health problems is argued as essential to successful interventions. However, there remains a lack of conceptual clarity around ‘participation’ in mental health interventions with the specific elements of participation rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In fact, the very idea of generalizable evidence today may be less challenged by social scientists than by novel RCT designs and realist evaluation methods, which no longer aim to produce universal and transferrable ‘proof of concept’ evidence but to answer to question: ‘What works, for whom, where, and why?’ (Heap et al, 2022). For example, sequential, multiple assignment, randomized trials (SMART) create iterative and adaptive interventions that get optimized along the way by switching participants from one group to another at different stages, which produces knowledge on the relative effectiveness of multiple intervention options, as well as aggregate profiles of the kind of people who would benefit from an intervention (Breuer et al, 2018; Maulik et al, 2015; Mukherjee et al, 2022).…”
Section: Making Middle-groundsmentioning
confidence: 99%
“…In fact, the very idea of generalizable evidence today may be less challenged by social scientists than by novel RCT designs and realist evaluation methods, which no longer aim to produce universal and transferrable ‘proof of concept’ evidence but to answer to question: ‘What works, for whom, where, and why?’ (Heap et al, 2022). For example, sequential, multiple assignment, randomized trials (SMART) create iterative and adaptive interventions that get optimized along the way by switching participants from one group to another at different stages, which produces knowledge on the relative effectiveness of multiple intervention options, as well as aggregate profiles of the kind of people who would benefit from an intervention (Breuer et al, 2018; Maulik et al, 2015; Mukherjee et al, 2022).…”
Section: Making Middle-groundsmentioning
confidence: 99%
“…Despite the problem of definitional slippage of the concept of "co-production" and the problem of cobiquity (a rise of different 'co' words describing collaborative practices) [23], there is some agreement in the literature on definitions. Heap et al [28] identify how different theorists repeatedly conceptualised degrees of participation as ladders or continuums with differences in terminology but which all range from "consumerism" to "democratisation." On these various scales, service users have little power or tokenistic participation at the bottom (consumerism), and at the top they are in control or share control (democratisation).…”
Section: Considerations For Defining Co-productionmentioning
confidence: 99%
“…But there is limited acknowledgement of the political and power dimensions at work within participatory approaches. Recently, along with colleagues, 17 we reviewed definitions of participation used within the development and global health landscape. We identified that most paradigms view participation as working to contribute to change through process, or outcome.…”
Section: The End (And To Begin Again): Long Live Transformationmentioning
confidence: 99%